True Brits - Daeschner J. R. (London, Arrow Books, 2004)
True Brits Daeschner This book is a trek around Britain, following American J.R. Daeschner as he meets some of the great British eccentrics who involve themselves in a host of bizarre pastimes, including hurling themselves down a grass hill in pursuit of a cheese and dancing around with reindeer antlers on their heads.